PCR-based detection of Theileria ovis in Rhipicephalus bursa adult ticks - Aktas, M.; Altay, K.; Dumanli, N. (Elsevier, 2006)
Tick-borne diseases in ruminants are common in tropical and subtropical regions and lead to meat and milk production losses. In this study, polymerase chain reaction (PCR) was used to assess the presence of Theileria ovis in Rhipicephalus bursa ticks. We have demonstrated that the PCR enabled detection of T. ovis in field isolates of R. bursa collected from naturally infested sheep and goats in eastern Turkey. The sampling was done in spring season (between May and June 2004). A total of 420 R. bursa were collected and randomly selected 192 number of them (97 female and 95 male) were dissected. Primers specific for 520 bp fragments small subunit ribosomal RNA (ssu rRNA) gene of T. ovis amplified products from 37 of the 192 (19.27%) samples. The parasite was detected in 17 (17.52%) female and in 20 (21.05%) male ticks. Two T. ovis amplicons from the tick samples were purified and sequenced. The resulting sequences were identical to the nucleotide sequence of the Turkish sheep strain of T. ovis. These results showed that R. bursa might play an important role in the field as a natural vector of T. ovis. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Rhipicephalus bursa; sheep and goats; Theileria ovis